2018
DOI: 10.1093/jrr/rry071
|View full text |Cite
|
Sign up to set email alerts
|

Controversial issues in radiotherapy after breast-conserving surgery for early breast cancer in older patients: a systematic review

Abstract: Breast cancer is the most common malignant disease among older women, and the number of new older patients per year is increasing year by year. Radiotherapy has been confirmed as an important treatment after breast conservation for the reduction of local recurrence and mortality for all patients, including node-positive cases. However, there are fewer clinical trials evaluating the toxicity and benefits of radiotherapy for older patients. Whether radiotherapy can provide substantial benefit for older patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…6 It is complex to manage a benefit/risk balance for elderly breast cancer patients, because it is necessary to weigh life expectancy, competing risk of death and treatment-related toxicity. 9 Although only a few deaths resulted from breast cancer in the C9343 trial, 7 our analysis of Surveillance, Epidemiology, and End Results Program (SEER) data between 2004 and 2014 showed that, among patients aged ≥70, approximately 20% of deaths that occurred within 5 years after cancer diagnosis were attributable to breast cancer. Noteworthy, the risk of dying from breast cancer also significantly increases with aging, especially for those aged ≥80.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6 It is complex to manage a benefit/risk balance for elderly breast cancer patients, because it is necessary to weigh life expectancy, competing risk of death and treatment-related toxicity. 9 Although only a few deaths resulted from breast cancer in the C9343 trial, 7 our analysis of Surveillance, Epidemiology, and End Results Program (SEER) data between 2004 and 2014 showed that, among patients aged ≥70, approximately 20% of deaths that occurred within 5 years after cancer diagnosis were attributable to breast cancer. Noteworthy, the risk of dying from breast cancer also significantly increases with aging, especially for those aged ≥80.…”
Section: Discussionmentioning
confidence: 97%
“…8 Nonetheless, the importance and necessity of RT after BCS in the elderly population remains considerably controversial. 9 In 2005, the National Comprehensive Cancer Network (NCCN) clinical practice guidelines included a recommendation that RT may be omitted in patients aged ≥70 who had ER+, clinically node-negative, T1 tumors and had received endocrine therapy. 4 Despite this, RT use in routine practice only declined minimally.…”
mentioning
confidence: 99%
“…A randomized trial study by Holli et al found that PRT does not increase OS in breast cancer patients 15. Similarly, Tang et al also suggested PRT should be considered with caution for female elderly breast cancer patients 6. However, another study conducted by Cosar et al found that elderly women with early breast cancer could significantly benefit from PRT 16.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis suggested radiotherapy could reduce the 10-year risk of any first recurrence and the 15-year risk of breast cancer death 3. The role of PRT is still controversial when the tumor size is ≤5 cm and the number of positive lymph nodes is between one and three 4-6. Certain studies suggest that radiotherapy may impair the quality of life in elderly patients 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…In a population-based study, the omission of RT after BCS even in the elderly and those who had an increased risk of recurrence was not acceptable because of the increasing potential of local recurrence and breast cancer mortality [32,33]. In older patients with low-risk breast cancer, RT in addition to hormonal therapy decreased the probability of local recurrences but did not improve OS [34].…”
Section: Discussionmentioning
confidence: 99%